Protection Devices Coordination in Distribution Systems with Microgrids Powered by Renewable Distributed Generation - Reiz, Cleberton; Leite, Jonatas B. (Institute of Electrical and Electronics Engineers (IEEE), 2022)
Microgrids are promising to enhance power distribution systems’ efficiency, quality, sustainability, and reliability. However, microgrids operation can impose several challenges to traditional protection schemes, like changes in the power flow direction and an increase in short-circuit currents. Microgrids can include several distributed generation technologies with different behaviours during short-circuit conditions, requiring additional protection schemes and devices. In this way, the optimized coordination of reclosers and fuses in distribution networks with directional overcurrent relays, which operate as interconnection devices, might overcome many imposed protection challenges. Regarding to different generation technologies, voltage-restrained overcurrent relays and frequency relays are presented as local microgrid protection for rotative and inverter-based distributed generators, respectively. The optimized coordination of these protection devices maximizes microgrid benefits and minimizes operation drawbacks by reducing interruptions impacts and energy not supplied to consumers. This work proposes, thus, a mathematical model for the optimal coordination of protection devices in distribution networks with distributed energy resources operating in grid-connected and islanded modes. The minimization technique of operating times using an elitist genetic algorithm with variable crossover and mutation processes is proposed, as well. The results show adequate coordination using passive and low-cost protection devices.
Keywords: Distribution networks; Fuses; Genetic algorithms; Genetic Algorithms; Microgrids; Optical character recognition; Power distribution planning; Power system protection; Relays; Short-circuit currents